PEMBUKTIAN KEKUATAN AKTA DI BAWAH TANGAN YANG DILEGALISASI OLEH NOTARIS - Ivanovich Suaedi; Munsyarif Abdul Chalim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
The verification of the power of a deed under the law legalized by a Notary who is responsible for the truth of the deed under his or her legalization is about the certainty of the signature that it is certain that the signature is indeed a party to the agreement, not someone else. The responsibility of a Notary in a Notary Law (UUJN) is explicitly mentioned in article 65 of the UUJN stating that a Notary replacement, a Notary of a Successor and a Notary Officer is responsible for each deed he has made, even though the notary protocol has been transferred or transferred to the depositary protocol. Accordingly, in the proof of a notarial deed by a notary publicly legalized by the notary does not have the perfect hill strength as it lies in the signature of the parties which, if acknowledged, is one of the most complete evidence.The method of approach used in this study is normative juridical research on the text of law alone, but involves the ability of scientific analysis of legal materials with the support of understanding the legal theory. Sources and Types of Data are based on primary legal material that is derived from the applicable Book of Law and secondary law materials consisting of reference books and Journals and scientific papers, research results relating to research materials.From the result of the research, it can be concluded that the power of deeds dehumanized by the Notary will be perfectly verified if the parties want and recognize the signature of the deed under the agreement which has been legalized by the Notary.Keywords: Legalization, Deed, Notary